Criteria for oral appliance and/or supine avoidance therapy selection based on outcome optimization and cost-effectiveness. (1st January 2021) - Levendowski, Daniel J.; Olmstead, Richard; Sall, Edward; Westbrook, Philip R.; Beine, Bretton; Munafo, Dominic
Abstract: Aim: Produce empirical support for further enhancements to a therapy selection protocol for obstructive sleep apnea (OSA) patients intolerant of positive airway pressure. Methods: A retrospective analysis was conducted in 101 men and 69 women patients. Two-night home sleep apnea studies were conducted at baseline and with a trial oral appliance. Twenty-minutes in-position sleep was required to compute supine and non-supine apnea-hypopnea indexes (AHI). Data analyses were applied after stratification by sex and response to oral appliance therapy (OAT), and the results used for to calculate incremental cost-effectiveness ratios (ICER). Results: Compared with men, women had significantly lower pre-treatment supine and non-supine AHI values ( p  < .05). OAT non-responders had higher non-supine AHIs, resulting in less positional-OSA and more cases with severe OSA ( p  < .05). Across the cohort, 21% had positional-OSA with a pre-treatment non-supine AHI < 5 events/h. In those who met this criterion, supine avoidance therapy (SAT) could have reduced the AHI values more than OAT by an average of 33% ( p  < .0001). The ICER for SAT instead of OAT in this group was negative, a condition that only occurs when one therapy is both less expensive and more effective than the other. A greater proportion of non-responders had post-OAT overall AHI ≥ 10 events/h with residual positional-OSA compared with responders ( p  < .0001). Combination therapy could reduce the AHI values by an average of 68%, resulting in ICER estimates five-times less than the reimbursement decision-making threshold. Conclusions and limitations: Based on pre-treatment non-supine AHI values, SAT would provide a superior first-line treatment outcome as compared to OAT in 21% of patients diagnosed with OSA. SAT would also provide a cost-effective adjuvant to OAT in an additional 15% of cases. The benefit of SAT could not be determined in one-fifth of the cohort who slept exclusively supine.